Pengaruh Kompensasi, Motivasi, Dan Budaya Organisasi Terhadap Kinerja Guru (Studi Pada SMP Negeri 1 Ngluwar Magelang) - Lisa Putri Nurrani (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study was conducted to analyze and describe the effect of compensation, motivation and organizational culture on teacher performance at SMP Negeri 1 Ngluwar.The population in this study were all teachers of SMP Negeri 1 Ngluwar as many as 50 people, with the sampling technique used was saturated sampling. Data collection with a questionnaire in the form of a google form link sent via the WhatsApp application. The hypothesis testing tool uses SPSS For Windows Version 17.0 software.From the results of the regression test, the motivation variable (X2) has the largest beta value, namely 0.405 organizational culture variable (X3) has a beta value of 0.374 compensation variable (X1) has a beta value of 0.026. The value of R Square shows a value of 0.573 or 57.3 this number means that the variation of the dependent variable (Y) can be explained by the independent variable (X) by 57.3%, while the remaining 42.7% is explained by other variables not in this study. In conclusion, all teachers at SMP Negeri 1 Ngluwar are influenced by compensation, motivation and organizational culture. However, the most dominant factor influencing teacher performance is the motivation variable. Keywords: Compensation, Motivation, Organizational Culture, Performance